Measurement of the cross section for electroweak production of Z gamma in association with two jets and constraints on anomalous quartic gauge couplings in proton-proton collisions at root s=8 TeV - Khachatryan, V. (2017)
A measurement is presented of the cross section for the electroweak production of a Z boson and a photon in association with two jets in proton-proton collisions at root s = 8 TeV. The Z bosons are identified through their decays to electron or muon pairs. The measurement is based on data collected with the CMS detector corresponding to an integrated luminosity of 19.7 fb(-1). The electroweak contribution has a significance of 3.0 standard deviations, and the measured fiducial cross section is 1.86(-0.75)(+0.90)(stat)(-0.26)(+0.34)(syst) +/- 0.05(lumi) fb, while the summed electroweak and quantum chromodynamic total cross section in the same region is observed to be 5.94(-1.35)(+1.53) (stat)(-0.37)(+0.43)(syst) +/- 0.13(lumi) fb. Both measurements are consistent with the leading-order standard model predictions. Limits on anomalous quartic gauge couplings are set based on the Z gamma mass distribution. (C) 2017 The Author. Published by Elsevier B.V.